Aplikasi Media Pembelajaran Menanam Sayuran Hidroponik Berbasis Android - Jerrycho Azarea Aditama; Jati Sasongko Wibowo (Elkom: Jurnal Elektronika dan Komputer, 2023)
Learning Media applications that use an Android-based material delivery system are expected to facilitate the delivery of material, where previously material was only found in books and the internet. Learning materials that only come from books reduce the reader's understanding because there are only text and pictures. This is what underlies the selection of the thesis title "Application of Android-Based Hydroponic Vegetable Growing Learning Media Application" in the hope that it can be a solution to help people who take part in the training understand material about growing vegetables by hydroponics.Hydroponics is an agricultural activity carried out by using water as a medium to replace soil. So, hydroponics can be interpreted as a work or management of water as a medium for plant growth without using soil media as a planting medium and taking the required mineral nutrients from a nutrient solution dissolved in water. The learning media application for growing hydroponic vegetables based on Android is limited to material on hydroponics, planting media and tools used in hydroponics, the steps needed for hydroponic farming, systems or techniques that exist in hydroponics.